FAKTOR MACROECONOMIC DAN BANK SPESIFIC DETERMINAN DARI PROFITABILITAS BANK DI INDONESIA DENGAN PENERAPAN INTERNET BANKING - Ossi Ferli (Indonesia Banking School, 2015)
The purpose of this research is to use a linier regression model and analyze the effect of macroeconomic and bank spesific factors to profitability of banks in Indonesia considering the implementation of internet banking. Spesifically we analyze the performance different between banks with internet banking and non internet banking. We use data of 30 banks in Indonesia periode of 2008 until 2010.The result shows that macroeconomic and some of bank spesific factors also internet banking has a significant influence to banks profitability. The research also showed bank with internet banking has a better performance than non internet banking, mostly because the overall condition of the banks and that internet banking has been a complementary factor in bank service to their customer.Keywords: Internet banking, data panel, bank spesific, macroeconomic